2018
DOI: 10.7575/aiac.ijalel.v.7n.4p.198
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Twitter Amongst Female Saudi EFL Learners

Abstract: Twitter is a popular microblogging site amongst the Saudi population, which means that Saudi EFL learners are now increasingly connected with millions of native English speakers and other EFL/ESL students. This paper shed light on the use of Twitter by female Saudi EFL learners to determine their English learning practices and their perceptions beyond formal learning contexts. Specifically, the research determined the manner by which the participants' social interactions over Twitter can help with second langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
1
11
0
2
Order By: Relevance
“…A considerable amount of research has been undertaken to examine the role of social media networks in learning (Aljaad, 2017;AlQahtani, 2018;Vivakaran & Neelamalar, 2018). Other investigations have explored students' attitudes and perspectives towards the use of social International Journal of Linguistics ISSN 1948-5425 2020 media networks in learning (Aifan, 2015;Alqarni et al, 2019;Bal & Bicen, 2017;Beqiri, 2014;Sharma, 2019;Ta'amneh, 2018) Although the literature is replete with studies regarding the use of such social media platforms as Facebook and Twitter for educational purposes (AbuSa'aleek, 2015;Alsharidi, 2018;Gamble & Wilkins, 2014;Junco et al, 2010;Kaya & Bicen, 2016;Razak et al, 2013), Instagram has not been studied in detail in terms of its use for educational purposes.…”
Section: Context Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of research has been undertaken to examine the role of social media networks in learning (Aljaad, 2017;AlQahtani, 2018;Vivakaran & Neelamalar, 2018). Other investigations have explored students' attitudes and perspectives towards the use of social International Journal of Linguistics ISSN 1948-5425 2020 media networks in learning (Aifan, 2015;Alqarni et al, 2019;Bal & Bicen, 2017;Beqiri, 2014;Sharma, 2019;Ta'amneh, 2018) Although the literature is replete with studies regarding the use of such social media platforms as Facebook and Twitter for educational purposes (AbuSa'aleek, 2015;Alsharidi, 2018;Gamble & Wilkins, 2014;Junco et al, 2010;Kaya & Bicen, 2016;Razak et al, 2013), Instagram has not been studied in detail in terms of its use for educational purposes.…”
Section: Context Of the Problemmentioning
confidence: 99%
“…Internet and social media websites make people live in a global village as they enable users to browse different websites concurrently (Ta'amneh, 2018). Social software technologies have become an integral part of individuals' life as well as English language learners' life as they enable learners to be frequently exposed to language due to their effective use of social platforms for learning or communication purposes (Alsharidi, 2018). The everyday use of the internet has played an active role in the improvement of students' English language and has brought significant changes in the way students use information (AlQahtani, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, la competencia ortográfica puede verse limitada por la ausencia de un corrector automático . Como aspecto positivo, sin embargo, se puede concluir que, por la exposición a la lengua, los mayores beneficios del microblogging tienen que ver con la adquisición de vocabulario y, por tanto, con un desarrollo de las competencias semántica y léxica (Alshahrani, 2017;Alsharidi, 2018).…”
Section: _________________________________________________ __________unclassified
“…Así pues, el microblogging genera transformaciones que permiten el desarrollo de competencias del siglo XXI como la autonomía, la creatividad y la comunicación, así como de competencias del Espacio Europeo de Educación Superior como la competencia en una lengua extranjera y la competencia digital (Alsharidi, 2018;Ruipérez et al, 2011). Las transformaciones, aunque positivas, se pueden ver frenadas en dos situaciones.…”
Section: _________________________________________________unclassified
“…What learning outcomes are identified in these studies? Most of the studies found a measurable and positive effect on students' writing (in terms of both quality and volume produced: Bataineh, 2014;Fattah, 2015;Said, 2015;Alsharidi, 2018); and comprehension of EFL (based on tests administered by researchers). WhatsApp and Twitter were found to be useful in supporting English language learning/teaching and are in fact the most popular SNSs in Saudi Arabia (Alsharidi, 2018;Fattah, 2015).…”
Section: What Are the Major Findings Across The Studies Reviewed?mentioning
confidence: 99%